Outcomes of infants with birthweights less than 501 g compared to infants weighing 501-750 g at a center utilizing first intention high frequency jet ventilation - Timothy G. Elgin; Jennifer N. Berger; Dinushan C. Kaluarachchi; John M. Dagle; Brady Thomas; Tarah T. Colaizy; Jonathan M. Klein (Frontiers Media S.A., 2024)
BackgroundData on clinical outcomes of infants with birthweights less than 501 g (ELBW<501) are limited.ObjectiveTo evaluate management strategies and clinical outcomes of ELBW<501infants compared to infants weighing 501-750 g (ELBW501-750).MethodsA retrospective study of all ELBW<501 and ELBW501-750 infants born between 2012 and 2022 at a center utilizing first intention high frequency jet ventilation was performed. Patient characteristics, clinical and outcome data were compared between the two groups.ResultsA total of 358 infants (92 ELBW<501 infants and 266 ELBW501-750) were included. The survival rate for the ELBW<501 group was 60.9% compared to 86.5% for ELBW501-750. ELBW<501 infants required more frequent use of 2.0 mm endotracheal tubes, required higher FiO2 and longer duration of mechanical ventilation. Compared to ELBW501-750 group, the ELBW<501 group were more likely to be SGA (68.2% vs. 16.5%) and more premature (23.2 vs. 24.3 weeks) with lower survival, longer length of stay, higher incidence of ROP and lower weight at discharge but comparable rates of IVH, grade 3 BPD, discharged on supplemental oxygen, and tracheostomy.ConclusionELBW<501 infants are at risk for significant morbidity and mortality. However, with specialized obstetric and neonatal care, survival rates of 60% are possible with respiratory outcomes comparable to ELBW501-750 infants. However, the increased risk of severe ROP for ELBW<501 requiring either surgical or medical intervention is concerning and warrants optimal surveillance.